Analysis on factors that affecting productivity of fresh fruit bunches in oil palm plantation / Mohamad Roslan Ahmad - Ahmad, Mohamad Roslan (2019)
A case study is to determine the factors that affecting productivity of fresh fruit bunches (FFB) in oil palm plantation. The study was conducted at Felcra Berhad Kawasan Lekir, Sitiawan, Perak. The secondary data were used in this study. The model was diagnosed for appropriate specification and the results of Ordinary Least Square (OLS) analysis method were preferred specification to examine the oil palm production function. Based on findings, proved that only two variables which are the rate of rainfall (LRF) and the quantity of fertilizer (LFT) have significant positive relationship with productivity of fresh fruit bunches (FFB). The study also recommends that the organizations or the stakeholders of the plantation should add more labor workforce to the estate and providing the good irrigation system and rainwater reservoir as a supply in the dry season.